A Molecular Dynamics Study on the Structure, Interfaces, Mechanical Properties, and Mechanisms of a Calcium Silicate Hydrate/2D-Silica Nanocomposite - Zhou, Yang; Zheng, Haojie; Qiu, Yuwen; Zou, Xixi; Huang, Jiale (Frontiers in Materials, 2020)
The incorporation of nano-reinforcements is believed to be a promising method to create high performance nanocomposites, which are largely dependent on the interfacial connections. In this work, the newly emerging two-dimensional (2D) material, 2D-silica is intentionally intercalated into the interlayer defective sites of calcium silicate hydrate (C-S-H), which is the primary hydration product of ordinary portland cements. The reactive molecular simulation results indicate the nano-reinforcement can strongly interact with the inorganic matrix to form a high-ductility nanocomposite. The uniaxial tensile loading tests show the plastic stage of the C-S-H is dramatically enhanced due to the intercalation of 2D-silica, which removes the intrinsic brittleness of cement-based materials at the nano-scale. It is observed that the dangling atoms at the edge of 2D-silica can react with non-bridging oxygen atoms of C-S-H, forming Si-O-Si bonds at interfaces. Those covalent bonds transform Q1 and Q2 in the C-S-H into high connectivity Q3 and Q4 species, which increases the integrity of the matrix and its resistance to crack propagation. During the tensile process, the elongation and breakage of those high-strength covalent bonds needs higher tensile stress and consumes higher energy, which leads to a strong plasticity and higher toughness. This work may shed new lights on the interaction mechanisms between 2D-materials and inorganic hosts, and provide solutions to modifying the brittleness of concrete.